2014
DOI: 10.1590/s0100-06832014000100032
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of land leveling on lowland soil physical properties

Abstract: SUMMARYThe practice of land leveling alters the soil surface to create a uniform slope to improve land conditions for the application of all agricultural practices. The aims of this study were to evaluate the impacts of land leveling through the magnitudes, variances and spatial distributions of selected soil physical properties of a lowland area in the State of Rio Grande do Sul, Brazil; the relationships between the magnitude of cuts and/or fills and soil physical properties after the leveling process; and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In a study carried out by Nunes et al (2002) in Albaqualf soils in the municipality of São João do Polêsine about 40 km northeast from the town of Santa Maria, researchers found that systematization increased soil subsurface density, due to the traffic of heavy machinery. Similarly, Parfitt et al (2014) found that the average BD of 1.60 Mg m -3 (prior to systematization) changed to 1.67 Mg m -3 as result of the systematization process and machine traffic. Thus, a denser soil layer in the areas of Experiment 1 may also be associated with the systematization process of the area.…”
Section: Discussionmentioning
confidence: 89%
“…In a study carried out by Nunes et al (2002) in Albaqualf soils in the municipality of São João do Polêsine about 40 km northeast from the town of Santa Maria, researchers found that systematization increased soil subsurface density, due to the traffic of heavy machinery. Similarly, Parfitt et al (2014) found that the average BD of 1.60 Mg m -3 (prior to systematization) changed to 1.67 Mg m -3 as result of the systematization process and machine traffic. Thus, a denser soil layer in the areas of Experiment 1 may also be associated with the systematization process of the area.…”
Section: Discussionmentioning
confidence: 89%
“…The presence of N in soil is important for SOC accumulation as C sequestration requires N (van Groenigen et al, 2017). Parfitt, Timm, Reichardt, and Pauletto (2014) reported that high pH (due to liming) possibly reduces SOC. The difference in SOC (%) between the cover crops and the control treatments was at its highest at low N fertilizer rate.…”
Section: Nghgb (Mean ± Sd)mentioning
confidence: 99%
“…High soil pH decreases the efficiency of cover crops to accumulate SOC. Parfitt, Timm, Reichardt, and Pauletto (2014) reported that high pH (due to liming) possibly reduces SOC. Both soil texture and tillage had no significant impacts on the efficiency of cover crops to sequester SOC, compared to control treatments.…”
Section: Influences Of Management Soil and Climatic Zones On Covermentioning
confidence: 99%
“…In the short term, land consolidation disturbed the nutrient status of the surface soil and thus negatively affected rice growth [2,44]. Previous studies have shown that soil physicochemical properties can have extremely significant effects in the short term after land consolidation [21,74], which include the severe compaction of soil, increased viscosity, decreased fertility, and decreased plant growth. Moreover, these adverse effects mainly occurred in the first growing season after land consolidation [30,31], when the soil layer was disturbed, especially the surface layer, and the topsoil physicochemical properties changed [20,30].…”
Section: Factors Influencing Of the Ndvi Value Of Rice Growthmentioning
confidence: 99%